The Relationship Between Family Support and Religiosity with Quality of Life in Breast Cancer Patients in Sukabumi, West Java Indonesia - Dewi, Rosliana; Panduragan, Santhna Letchmi; Umar, Nur Syazana (STIKep PPNI Jawa Barat, 2025)
Background: As a major public health concern on a worldwide scale, breast cancer impacts not just the physical health of patients but also their mental, emotional, social, and spiritual well-being, frequently leading to a decline in QoL. Although both family support and religion are known to have a significant impact on quality of life, the combined impacts of these two characteristics have not been thoroughly studied, especially in the cultural setting of Indonesia. Objective: The purpose of this research is to look at how breast cancer patients in Sukabumi, West Java, Indonesia, fare when it comes to family support, religious affiliation, and quality of life. Methods: The 320 women diagnosed with breast cancer at four different Sukabumi hospitals participated in a quantitative cross-sectional study that took place in 2020 and 2021. To gather data, researchers used validated instruments such as the EORTC QLQ-C30 for quality of life, the Family Support Scale for family support, and the Duke University Religion Index (DUREL) for religiosity. The associations between variables were examined using descriptive and inferential methods, including multiple regression. Results: The mean scores for family support, religiosity, and QoL were 12.51 (SD = 2.161), 22.89 (SD = 3.554), and 44.04 (SD = 8.556), respectively. Simple regression analysis revealed significant positive relationships between family support (B = 2.718, p < 0.001, R² = 47.1%) and religiosity (B = 1.664, p < 0.001, R² = 47.8%) with QoL. Multiple regression analysis indicated that family support and religiosity jointly explained 57.2% of the variance in QoL (p < 0.001). Quality of life (QoL), family support (12.51; SD= 2.161), and religion (22.89; SD= 3.554) had respective mean ratings of 44.04 (SD= 8.556). The results of the simple regression analysis showed that religiosity (B = 1.664, p < 0.001, R² = 47.8%) and family support (B = 2.718, p < 0.001) were significantly positively correlated with quality of life (QoL). According to multiple regression analysis, 57.2% of the variation in quality of life (QoL) was explained by both family support and religion (p < 0.001). Conclusion: Religion and the support of family members are important factors in determining quality of life for breast cancer patients. Their combined impact highlights the significance of care options that incorporate spiritual and familial support. These results give light on how to improve the quality of life and holistic treatment for breast cancer patients in Indonesia by creating interventions that are culturally specific.